Advanced Transmission Electron Microscopy for Identification of Atomic‐Scale Configurations of Zeolite‐Supported Metal Catalysts. Issue 19 (29th July 2022) - Tang, Xuan; Ye, Jiajie; Guo, Yun; Dai, Sheng
Abstract: Zeolite‐supported metal catalysts have important applications in various catalytic reactions, but unveiling their atomic‐scale structures is always a grand challenge. The developed transmission electron microscopy (TEM) characterization techniques, e.g ., integrated differential‐phase contrast (iDPC) scanning transmission electron microscopy (STEM) is emerging as a powerful tool for visualizing the electron beam‐sensitive materials at atomic resolution, thus, providing new opportunities for imaging the exact configurations of metal species in the various channels of zeolites. This emerging topic summarizes recent progress utilizing iDPC‐STEM‐related technique for determination of the structures of metal species in zeolites that should offer insights into the structure‐property relationships of zeolite‐supported metal catalysts. A brief perspective about the new TEM technique is also presented, showing prospects in this field that will stimulate further scientific research in zeolite‐supported metal catalysts. Abstract : The emerged iDPC‐STEM‐related techniques provide new opportunities for imaging the exact configurations of metal species in the various channels of zeolites.